Impacts of employee engagement, self-efficacy, self-esteem, and organisational citizenship behaviour on job performance of academic staff in University Tunku Abdul Rahman (UTAR) during the covid-19 pandemic - Ang, Huey Shin; Heng, Se Ti; Lee, Sook Yan; Sing, Xiao Xuan (2022)
The outbreak of Covid-19 has implied significant effects on organisations’ way of management, affecting employees’ working routines and activities. Recently, we found that the job performance of academic staff had been influenced by the Covid-19 pandemic. Hence, this research is to investigate the impacts of employee engagement, self-efficacy, self-esteem, and organisational citizenship behaviour on the job performance of academic staff in Universiti Tunku Abdul Rahman (UTAR) during the Covid-19 pandemic. Specifically, the study sought to achieve the following: (1) To investigate the impact of employee engagement on the job performance of academic staff in UTAR during the Covid-19 pandemic; (2) To determine the impact of self-efficacy on the job performance of academic staff in UTAR during the Covid-19 pandemic; (3) To study the impact of self-esteem on the job performance of academic staff in UTAR during the Covid-19 pandemic; (4) To examine the impact of organisational citizenship behaviour on the job performance of academic staff in UTAR during the Covid-19 pandemic.